The Determinants of Corporate Hedging Policy: A Survey of Mining Firms on the Indonesia Stock Exchange - Nugraha, Mahardika Dandy; Khoiruddin, Moh (Universitas Negeri Semarang, 2022)
The purpose of this study is to determine the effect of leverage, liquidity, growth opportunity, and financial distress on hedging policy decisions. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020. The research sample was 39 companies using purposive sampling technique. The leverage variable is proxied by the ratio of total debt and total capital, liquidity is proxied by the ratio of current assets and current debt, growth opportunity is proxied by market to book, financial distress is proxied by Altman's Z-Score specifically for non-manufacturing companies, and hedging policy is proxied by the variable dummy, where companies that hedged were given a score of 1, and those that did not hedge were assigned a score of 0. The data analysis method used descriptive statistical analysis and logistic regression analysis using the logit model using the Eviews 12 Student Version software. The results showed that leverage and financial distress had a significant positive effect on the probability of hedging policy, liquidity had a significant negative effect on the probability of hedging policy, growth opportunity had a significant positive effect on the probability of hedging policy